Analysis on equity of health service utilization and influencing factors in patients with hypertension in China: a longitudinal study - Yang, Xiaoqian; Lin, Chunmei; Qin, Jiangmei; Zhang, Yanchun; Zhang, Lifang (BMC health services research, 2024)
Hypertension has become a major public health and social problem endangering the health of Chinese residents, and has brought a large economic burden of diseases to families and even the whole society. Promoting the equity of health service utilization for patients with hypertension is of great significance for reducing the occurrence of cardiovascular and cerebrovascular diseases and reducing the economic burden of patients with hypertension. This study aims to analyze the equity and change of outpatient and inpatient service utilization in patients with hypertension, and to explore its influencing factors. Using the data of Household Health Interview Survey from 34 key points of contact for comprehensive healthcare reform in 17 provinces in 2014 and 2016, the equity and change of outpatient and inpatient service utilization of patients with hypertension were analyzed by concentration index, and the contribution degree of each influencing factor to utilization inequality was analyzed by decomposition of concentration index. In 2014 and 2016, the standardized concentration index of two-week visits of hypertension patients was 0.0217 and 0.0141, respectively, indicating that the utilization of outpatient services was basically equitable. The standardized concentration index of times of hospitalization was 0.1593 and 0.1364, and the standardized concentration index of hospital length of stay was 0.1517 and 0.1369, respectively. The rich groups utilized more hospitalization services. Compared with 2014, the concentration index of outpatient and inpatient service utilization of patients with hypertension decreased in 2016, indicating that the inequity of outpatient and inpatient service utilization has further improved. The level of family income was the primary factor affecting the inequality of hospitalization utilization. The utilization of outpatient services in patients with hypertension was basically equitable; however, wealthier groups had greater utilization of inpatient services. Overall, the degree of inequity has been reduced. Family economic status was the main factor affecting inequality in utilization of medical services. To achieve common prosperity was the most fundamental measure to improve the inequitable utilization of hospitalization services. At this stage, we should improve the medical assistance system and increase the assistance to vulnerable groups, such as the low-income groups.